2015
DOI: 10.3109/00207454.2014.982795
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Parkinson's disease: role in neurodegeneration and tissue repair

Abstract: Neuroinflammation in Parkinson's disease [PD] is a process that occurs alongside the loss of dopaminergic neurons, and is associated with alterations to many cell types, most notably microglia. This review examines the key evidence contributing to our understanding of the role of inflammation-mediated degeneration of the dopaminergic (DA) nigrostriatal pathway in PD. It will consider the potential role inflammation plays in tissue repair within the brain, inflammation linked gene products that are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 78 publications
0
77
0
4
Order By: Relevance
“…When the number of dopamine-producing cells in the substantia nigra falls to less than 20-40%, then the symptoms of PD such as bradykinesia (slowness and minimal movement), rigidity, resting tremor and postural instability appear [82]. However, the exact molecular mechanisms contribute to this neuronal loss still remained to be clarified, it is thought that neuroinflammation, oxidative stress and mitochondrial dysfunction may play essential roles in PD pathogenesis (reviewed in [83,84]). Furthermore, it is also revealed that some environmental (such as exposure to pesticides or a toxin in the food supply) and genetic factors might be involved in the pathogenesis of certain forms of PD [82,85].…”
Section: Gsk-3␤ In Parkinson's Diseasementioning
confidence: 99%
“…When the number of dopamine-producing cells in the substantia nigra falls to less than 20-40%, then the symptoms of PD such as bradykinesia (slowness and minimal movement), rigidity, resting tremor and postural instability appear [82]. However, the exact molecular mechanisms contribute to this neuronal loss still remained to be clarified, it is thought that neuroinflammation, oxidative stress and mitochondrial dysfunction may play essential roles in PD pathogenesis (reviewed in [83,84]). Furthermore, it is also revealed that some environmental (such as exposure to pesticides or a toxin in the food supply) and genetic factors might be involved in the pathogenesis of certain forms of PD [82,85].…”
Section: Gsk-3␤ In Parkinson's Diseasementioning
confidence: 99%
“…Behind the protection of the BBB, however, CNS-specific immune effector cells, particularly microglia (Streit et al, 2004), mediate neuroinflammatory responses to insult in response to a variety of triggers, including toxic metabolites, autoimmunity (Gendelman, 2002) or via the detection of pathogens or endogenous damage-associated molecular patterns (PAMPs and DAMPs) released in response to CNS damage, such as traumatic brain injury (Bernier, 2012). The outcome of a neuroinflammatory response depends, to a large extent, on its severity and duration (Vivekanantham et al, 2015), but pathological neuroinflammation, promoting apoptosis and necrosis and influencing the synaptic and intrinsic membrane properties of neurons (Yirmiya and Goshen, 2011), contributes to a host of CNS pathologies. A central role for neuroinflammation has been reported for primary or secondary neurodegenerative diseases, such as Alzheimer's disease (AD), Parkinson's disease (PD), multiple sclerosis (SM) amyotrophic lateral sclerosis (ALS), Huntington's disease, stroke and epilepsy (Frank-Cannon et al, 2009).…”
Section: Introduction E the Evolution Of The Concept Of Neuroinflammamentioning
confidence: 99%
“…Accumulating evidence from various scientific studies suggests that neuroinflammation is one of the important factors involved in the selective degeneration of the nigral neurons in PD [1,2,3,4]. Extracts from medicinal plants and their secondary metabolites have conventionally been used to treat numerous clinical diseases, including inflammation-associated diseases [5].…”
Section: Introductionmentioning
confidence: 99%